2021
DOI: 10.12938/bmfh.2020-061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a high-γ-polyglutamic acid-containing natto diet on liver lipids and cecal microbiota of adult female mice

Abstract: Natto is a traditional Japanese fermented soy product high in γ-polyglutamic acid (γ-PGA), whose beneficial effects have been reported. We prepared high-γ-PGA natto and compared the dietary influence on liver lipids and cecal microbiota in mice fed a diet containing it or a standard diet. The mice were served a 30% high-γ-PGA natto diet (PGA group) or standard diet (Con group) for 28 days. Liver lipids, fecal lipids, and fecal bile acids were quantified. Cecal microbiota were analyzed by PCR amplification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Hepatic steatosis suddenly decreases egg output and quality, and fatty liver haemorrhage syndrome (FLHS) kills thousands commercial laying hens ( Liu et al, 2022 ). Coriobacteriaceae was discovered to be relatively common in NAFLH and associated illnesses, with significantly higher AST levels ( Tamura et al, 2021 ). Firmicuts and Actinbacteria were positively correlated with AST and ALP ( Hamid et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic steatosis suddenly decreases egg output and quality, and fatty liver haemorrhage syndrome (FLHS) kills thousands commercial laying hens ( Liu et al, 2022 ). Coriobacteriaceae was discovered to be relatively common in NAFLH and associated illnesses, with significantly higher AST levels ( Tamura et al, 2021 ). Firmicuts and Actinbacteria were positively correlated with AST and ALP ( Hamid et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment with natto extract significantly delay the accumulation of lipofuscin, a characteristic of aging cells Ibe, Kumada, Yoshida, & Otobe, 2013 Regulation of gut microbiota Natto, peanut meal extract fermented by B. subtilis natto Natto fermentation products from peanut meal can significantly improve the richness, diversity and uniformity of gut microbiota in antibiotic-induced diarrhoea mice Jiang et al, 2020 , Dimidi et al, 2019 Prevention of nonalcoholic fatty liver disease (NAFLD) High γ -polyglutamic acid (high- γ -PGA) natto Hepatic lipid accumulation typically facilitated the onset of nonalcoholic fatty liver disease (NAFLD). The liver lipid contents, the liver triglyceride contents and the liver cholesterol contents were found to be significantly lower in the PGA group mice fed a 30% high γ -PGA natto diet than those mice served standard diet in the control group Tamura et al, 2021 Decrease blood sugar, amelioration insulin resitance Natto and viscous vegetables combined with white rice The consumption of natto and viscous vegetables combined with WR improved the postprandial blood glucose and insulin profiles in subjects with impaired glucose tolerance (IGT). In addition, the consumption of natto and viscous vegetables in a Japanese style breakfast for two weeks improved insulin sensitivity, lipid profile and oxidative stress in subjects Taniguchi-Fukatsu et al, 2012 Prevention of breast cancer Natto lipopeptides Natto lipopeptides could change the expression levels of estrogen-receptor-α and estrogen-receptor-β and damage DNA of MCF-7 cells, a kind of human breast cancer cell, and therefore inhibit the proliferation of them and induce their apoptosis significantly Liu et al, 2015 , An et al, 2014 Antihyperlipidemia effect Natto enzyme powder Natto enzyme powder can significantly decrease the levels of total cholesterol, triglyceride and malonaldehyde and low-density lipoprotein cholesterol, and increase the level of total superoxide dismutase and high-density lipoprotein cholesterol.…”
Section: Pharmacological Actions Of Nattomentioning
confidence: 99%
“…Miso exerts an antioxidant effect by improving the 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging ability 63,64 . [45][46][47][48] Having antioxidant effect 63,64 Having the effect of decreasing of insulin resistance 48 Natto ↑: genera Bifidobacterium, Blautia, and Bacilli in human ↓: phylum Actinobacteria and genera Coriobacteriaceae_UCG-002, Bacteroides, and Lactococcus in mice; class Clostridia and family Enterobacteriaceae in human [49][50][51] Having antioxidant effect 72 and anti-inflammatory effect 74 . Inhabitation of glucose uptake by human intestinal cells 75 and dipeptidyl peptidase IV inhibitory activity 76 Cheonggukjang ↑: genera Coprococcus, Bifidobacterium, and Ruminococcus in human; orders Bacillales, Lactobacillales, and Verrucomicrobiales (Akkermansia muciniphila) in rat ↓: genera Sutterella, Escherichia/Shigella, and Collinsella in human; order Enterobacterales in rat 52,53 Having protective effect against apoptosis, inflammation, and oxidative stress 23 .…”
Section: In Vitromentioning
confidence: 99%
“…Animal study revealed that natto exerts antioxidant effects 72 and anti‐inflammatory effects by increasing IL‐10 levels 73 . A study using an animal model reported that natto consumption suppresses fatty liver 74 .…”
Section: Potential Beneficial Effect Of Fermented Soybean Foods On Di...mentioning
confidence: 99%